Dynamic Optimization Of Low Density Polyethylene Production In Tubular Reactor Under Thermal Safety And Fouling Resistance Constraints - Azmi, Ashraf (2019)
The highly exothermic nature of the low density polyethylene (LDPE) polymerization process and the heating-cooling prerequisite in tubular reactor can lead to thermal runaway and can also create fouling problems. Both problems need to be considered when optimizing the LDPE production to ensure the highest profit and a safe operation can be achieved. However, this is not an easy task since the conversion of the monomer (XM), which is normally proportional to high profits, could be achieved at high reaction temperatures and could lead to a high fouling formation. Consequently, in this work, the dynamic optimization study to obtain the optimum production of the LDPE under thermal safety and fouling resistance constraints is carried out. Prior to the dynamic optimization study, the kinetic rate parameters estimation is carried out. A mathematical model is developed and validated using industrial data. For thermal safety considerations, a suitable form of energy balance is developed and the reactor critical temperature ( ) is determined. For the fouling study, fouling resistance (Rf) is used as the fouling measurement. This study uses the changes in the heat transfer coefficient (U) determined from industrial data in order to obtain the maximum reactor fouling resistance. Based on the sensitivity studies, monomer flow rate (FM), initiator flow rate (FI), solvent flow rate (FS) and reactor inlet pressure (Pin) are selected as the optimized parameter variables while reactor jacket temperature (TJ) is selected as the optimized control variable in the dynamic optimization. In the dynamic optimization study, the optimization problems are solved using dynopt coded programming which is based on orthogonal collocation (OC) and sequential quadratic programming (SQP) methods. In different constraints case studies, the results show that the optimization case without thermal safety and fouling resistance constraints gives a higher XM than the optimization case with and constraints. Five different objective functions (OF) are considered to identify the most optimum reactor performance. The thermal safety and fouling resistance constraints are considered and are successfully satisfied in all the cases. The highest of 365.99 ℃ and of 49.48 cm2. s.K /cal are obtained by maximum XM and maximum profit OFs, respectively. These values are below the and allowed which are 366 ℃ and 50 cm2. s.K /cal, respectively. The most optimum reactor output is obtained from the maximum profit OF with the profit earned of RM328.18 million/year while the and ,sucessfully satisfied at 365.87 ℃ and 49.48 cm2.s.K/cal respectively. Overall, the complex relation of the LDPE tubular reactor process parameters and the trade-off balance between the input-output parameters are handled very well by the dynamic optimization.